Character Development Model of Kindergarten Students' Discipline Based on Eduparenting in Lombok, Indonesia - Rabiatul Adwiyah; Annisa Failasufa; Nani Nuriani; Kurniawati Astuti; Azalia Rizkini Pratiwi; Alya Tara Putri; Lalu Sumardi (Lafadz Jaya Publisher, 2024)
This study aims to analyze the model of character development of discipline in children at Pembina Sikur State Kindergarten and parenting education efforts implemented by parents at home. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The instruments used include observation sheets for the development of children's discipline character. Data analysis was carried out using the Miles and Huberman technique, which includes data reduction, data presentation, and drawing conclusions. The results of the study showed that the “Morning Journal” model implemented in schools was effective in improving children's disciplined character. This model involves collaboration between schools and parents, through parenting education activities such as